Synthesis of Core–Double Shell Nylon-ZnO/Polypyrrole Electrospun Nanofibers - Beregoi, Mihaela (Nanomaterials (Basel), 2020)
Core–double shell nylon-ZnO/polypyrrole electrospun nanofibers were fabricated by combining three straightforward methods (electrospinning, sol–gel synthesis and electrodeposition). The hybrid fibrous organic–inorganic nanocomposite was obtained starting from freestanding nylon 6/6 nanofibers obtained through electrospinning. Nylon meshes were functionalized with a very thin, continuous ZnO film by a sol–gel process and thermally treated in order to increase its crystallinity. Further, the ZnO coated networks were used as a working electrode for the electrochemical deposition of a very thin, homogenous polypyrrole layer. X-ray diffraction measurements were employed for characterizing the ZnO structures while spectroscopic techniques such as FTIR and Raman were employed for describing the polypyrrole layer. An elemental analysis was performed through X-ray microanalysis, confirming the expected double shell structure. A detailed micromorphological characterization through FESEM and TEM assays evidenced the deposition of both organic and inorganic layers. Highly transparent, flexible due to the presence of the polymer core and embedding a semiconducting heterojunction, such materials can be easily tailored and integrated in functional platforms with a wide range of applications.